Capacity Building on Public Policy Analysis Tools in Colombia #NPSinitiative - Castillo, Johana; Salas, Daniela (CGIAR System Organization, 2024)
The joint effort of the Alliance of Bioversity and CIAT, in partnership with the International Food Policy Research Institute (IFPRI), has been instrumental in promoting and strengthening the integration of policy and investment tools in Colombia through the CGIAR Research Initiative on National Policies and Strategies (NPS). The second part of the course, “Policy Analysis Tools using General Equilibrium Models for Colombia” was held in this framework, a three-day face-to-face program last March 12 and 14, 2024 with the Agrifood Systems Research Center of the University of Los Andes, in Bogotá. At this stage, participants developed skills in public policy analysis tools using general equilibrium models and their adaptation to the Colombian case to improve decision-making in their respective fields of action.